On Gradings of the Operator Algebra Generated by Mapping and Multipliers - E.V. Patrin (Учёные записки Казанского университета: Серия Физико-математические науки)
The operator algebra generated by mapping on a countable set and multipliers is considered. The defined mapping induces a family of partial isometries satisfying some relations. These isometries, as well as the multipliers, are the generators of the investigated algebra. We equip the algebra with a torus action and consider the corresponding covariant system.